Pulmonary Embolism Response Teams - Witkin, Alison S.; Harshbarger, Savanah; Kabrhel, Christopher (Seminars in Thrombosis and Hemostasis, 2016)
Pulmonary embolism is a common and often life-threatening event. Treatment options include anticoagulation alone, catheter-directed therapies, and surgical thromboembolectomy. While guidelines exist, there is often controversy over which treatment is most appropriate, particularly for intermediate-risk patients. The traditional care model, in which the primary team is responsible for consulting the appropriate specialists, may be inadequate and inefficient for emergent situations, as ensuring coordination and communication between various consulting services can be a time consuming and confusing process. The Pulmonary Embolism Response Team (PERT) model was developed to improve the quality and efficiency of care for patient with intermediate- and high-risk pulmonary embolism. Activation of the PERT allows for rapid, multidisciplinary discussion among dedicated specialists, which typically includes members of the cardiology, emergency medicine, hematology, pulmonary/critical care, and surgical services. While the majority of patients are still treated with anticoagulation alone, in the event that a more invasive approach is deemed necessary, the team expedites this process. Over the last several years, the PERT model has been adopted at more than 75 health care institutions and may represent a new standard of care.
Keywords: pulmonary embolism; deep vein thrombosis; rapid response team; thrombosis; thrombolysis